ORIGINALITY OF THE TEXRS OF SHAKESPEARE’S DRAMAS AND THEIR TRANSLATION INTO UZBEK - Fayziyeva.K.; Boboyorova Marjona Akbar qizi (TADQIQOTLAR, 2026)
Abstract This article explores the originality of the texts of William Shakespeare’s dramas and examines the challenges and strategies involved in translating his works into Uzbek. It analyzes the literary and linguistic features that contribute to the uniqueness of Shakespeare’s writing, including his use of language, poetic devices, and cultural references. The study also assesses how these elements are preserved or adapted in Uzbek translations, highlighting the importance of maintaining the playwright’s artistic intent and emotional impact.